Insights into adoption of farming practices through multiple lenses: an innovation systems approach*. Issue 8 (17th November 2018) - Clarke, Elizabeth; Jackson, Tamara M.; Keoka, Khamlouang; Phimphachanvongsod, Viengsavanh; Sengxua, Pheng; Simali, Phetsamone; Wade, Len J.
ABSTRACT: A complex systems approach to innovation provides rich insights into the drivers, barriers, and key elements for innovation in rural systems. Through a case study of dry direct seeding (DDS) in smallholder systems in Laos, this article reveals a "perfect storm" of challenges and opportunities resulting in rapid adoption. Labour shortage, climate variability, and machinery availability are key factors. The lessons for the research and development community are that; every local system and situation is unique; focusing on one set of factors is never sufficient; and that timelines for change may be long and require persistence and longer term commitment from donors.